Rhabdomyosarcoma: From Obscurity to Clarity in Diagnosis … But With Ongoing Challenges in Management: The Farber-Landing Lecture of 2020. (April 2021) - Parham, David M; Giannikopoulos, Petros
Rhabdomyosarcoma, the most common soft tissue sarcoma in childhood, has challenged and intrigued soft tissue pathologists ever since the original descriptions. Once based on the identification of rhabdomyoblastic cells with elongate eosinophilic cytoplasm, the diagnosis has evolved to include tumors composed only of primitive mesenchymal cells but now relies heavily on immunohistochemical stains for desmin, myogenin, and MyoD. Rhabdomyosarcomas show a variety of histological patterns, giving rise to classifications that have included embryonal, alveolar, botryoid, pleomorphic, spindle cell, and sclerosing subtypes. These have been linked to prognosis and treatment assignment in the past, but that concept has been superseded by the identification of PAX3-FOXO1 or PAX7-FOXO1 fusions. Fusion testing results are more predictive of outcome and have become standard practice in clinical management. However, high risk tumors with alveolar histology or metastatic disease continue to resist oncologic treatment.